NEW METHODS AND FACILITIES OF MAGNETIC CONTROL OF THE MECHANICAL CHARACTERISTICS OF ARTICLES - V. F. Matjuk; M. A. Meljguj (Литьë и металлургия)
There are given the results of development in the State scientific university ''Institute of applied physics of the National Academy of Sciences of Belarus” of the facilities for magnetic control of the steels mechanical characteristics - coercimeter KIPF-1, impulse magnetic analyzers IMA- 4M, IMA-5B, impulse magnetic installations IMPOK-IB and facilities of their metrological support. The information about the scale of , using IS given.